Pregnancy outcomes of Covid-19 possitive pregnant women at the Hue Central Hospital - Minh, Dinh Thi Phuong; Phim, Bui; Tung, Le Phuoc Binh; Tai, Tran Viet; Son, Hoang Ngoc; Nha, Nguyen Thi Thanh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2024)
Aim: To investigate some clinical and paraclinical characteristics and pregnant outcomes of pregnant women with COVID-19 at COVID-19 Research and Treatment Central of Hue. Methods: This retrospective observational study included all identified COVID-19- positive pregnant women admitted to the Hue Central Hospital – Branch 2 at labour from September 2021 to March 2022. Maternity and newborns were followed until discharge from the hospital. Results: Eighty-three pregnant women were positive for COVID-19. There were 32.5 % asymptomatic cases, 43.4 % had mild symptoms, while 21,1 % had more severe forms of the disease. The main follow-up morbidities were high BMI 24,1 %, anaemia 22.9 %, hypertensive disorders 4.8% and diabetes 2.4 %. The rate of premature births was 12.3%. There are 3/83 pregnant women with twins (3.6 %). Caesarean section was done for 63.9 % of women while 36.1 % delivered vaginally. Previous caesarean section (30.2%) was the most common indication for operative completion of labour. Eighty-five (98.8%) live babies were born, of which 11 (13.3%) were admitted to the neonatal intensive care unit. One baby (1.2%) died shortly after birth due to multiple malformations. Two infants (2.3 %) had a positive PCR test for COVID-19. Conclusion: Most pregnant women infected with COVID-19 are asymptomatic and mild. Almost pregnant women recovered well after giving birth, but 2 mothers died due to severe development of COVID-19 (their children’s lives were saved). 11 babies needed care in the NICU, one baby (1.2%) died soon after birth due to multiple malformations/prematurity. Two infants (2.3 %) had a positive PCR test for COVID-19.